Actions on Polish Spaces and p-Continuous Functions - Mohammed, Assakta (Journal of Pure & Applied Sciences, 2022)
The action of A on X is a map,F , called an f-action, which satisfies some conditions. In this paper, some results on f-actions are proved. First, the notion of p-continuity is defined. Using the properties of set-valued functions, we provide some results concerning the measurability, expansiveness, and extension of p-continuous f-actions, in the realm of Polish spaces. The findings of this paper generalize and extend some results in the literature.